2007
DOI: 10.1111/j.1365-2567.2007.02575.x
|View full text |Cite
|
Sign up to set email alerts
|

BCG stimulated dendritic cells induce an interleukin‐10 producing T‐cell population with no T helper 1 or T helper 2 bias in vitro

Abstract: SummaryMycobacterium bovis bacillus Calmette-Guérin (BCG) vaccine has been associated with beneficial effects on overall childhood mortality in lowincome countries; this cannot be explained merely by the prevention of tuberculosis (TB) deaths. The beneficial effects of BCG vaccine could be the result of either strengthening of pro-inflammatory mechanisms, helping neonates to fight infections, or the induction of an immune-regulatory network restricting overt inflammation and intense pathology. We aimed to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
32
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 38 publications
5
32
1
Order By: Relevance
“…In fact unvaccinated children at 4 1/2 mo of age had greater levels of IL-10 in BCG cultures than the BCG vaccinated individuals, suggesting that mycobacterial induced IL-10 could play a role in attenuating induction of the protective mycobacterial response after BCG vaccination. A lack of IL-10 upregulation after BCG vaccination is in conflict with other studies (46,47,58). A South African study showed upregulation of IL-10, albeit at very low levels (,0.01% of CD4 + or CD8 + T cells) in 12 h BCG cultures (47).…”
Section: Discussioncontrasting
confidence: 51%
“…In fact unvaccinated children at 4 1/2 mo of age had greater levels of IL-10 in BCG cultures than the BCG vaccinated individuals, suggesting that mycobacterial induced IL-10 could play a role in attenuating induction of the protective mycobacterial response after BCG vaccination. A lack of IL-10 upregulation after BCG vaccination is in conflict with other studies (46,47,58). A South African study showed upregulation of IL-10, albeit at very low levels (,0.01% of CD4 + or CD8 + T cells) in 12 h BCG cultures (47).…”
Section: Discussioncontrasting
confidence: 51%
“…Signaling between cells may aid these responses because lymphocytes produce IL-10 in response to various bacteria such as Mycobacteria spp. (75,76) and Helicobacter spp. (77), and intercellular interactions can be essential to drive antibacterial responses (78).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, mycobacteria, including the vaccine strain M. bovis bacillus Calmette-Guérin (BCG), are able to suppress the immune response by interfering with the normal function of DCs (23,73). Induction of the immunosuppressive cytokine interleukin-10 (IL-10) has a negative effect on the production of the proinflammatory cytokine IL-12 and inhibits a Th1-biased response which is necessary for mycobacterial clearance (14,45). Responsible for at least part of this immune modulation is the binding of mycobacteria to the C-type lectin DCspecific intercellular adhesion molecule 3-grabbing nonintegrin (DC-SIGN [CD209]) (26,69).…”
mentioning
confidence: 99%